Application of Maggot Fertilizer and Rock Phosphate on NPK Content of Gold Mine Soil: Aplikasi Pupuk Maggpt dan Batuan Fosfat Alam terhadap Kandungan NPK Tanah Pasca Penambangan Emas - Anggarisma, Albina Pamukti; Saidi, Didi (Universitas Pembangunan Nasional Veteran Yogyakarta, 2024)
Post-gold mining soils are generally characterized by acidic pH, low organic carbon (C-organic) content, and poor macronutrient levels, particularly nitrogen (N), phosphorus (P), and potassium (K). This study aimed to evaluate the effect of applying organic fertilizer derived from maggot livestock waste and natural phosphate rock on soil pH, C-organic, and N, P, and K content in post-gold mining land. The research employed a factorial completely randomized design (CRD). The first factor was maggot-based organic fertilizer applied at three rates: 0 g/pot, 8.3 g/pot, and 16.6 g/pot. The second factor was natural phosphate rock, also at three rates: 0 g/pot, 0.16 g/pot, and 0.33 g/pot. This resulted in 9 treatment combinations, each replicated 3 times, for a total of 27 experimental units. Soil parameters analyzed included pH, C-organic, total N, available P, and available K. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level where applicable. The results indicated that maggot fertilizer significantly increased the availability of P and K, while natural phosphate rock significantly increased available P. A significant interaction between maggot fertilizer and phosphate rock was observed for soil pH. The optimal combination for improving pH was the application of 20 tons/ha of maggot fertilizer (equivalent to 16.6 g/pot) and 400 kg/ha of natural phosphate rock (equivalent to 0.33 g/pot).